SISTEM INFORMASI MANAJEMEN YAYASAN DALAM PENGELOLAAN KEUANGAN DI LEMBAGA PENDIDIKAN - Mira Febrina; Supratman Zakir (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract. The application (SIMKU) for the foundation's financial management information system is an application with an online computerized system based on an integrated and comprehensive web application so that it can be accessed anywhere and at any time. This research includes library research. Data collection techniques include editing (rechecking the data obtained), organizing (organizing the data obtained using a research framework), and finding (further analysis of the results of organizing the data). The data analysis technique in this research was carried out by reading, reviewing and analyzing various existing literature. The implementation of SIM can contribute to increasing efficiency, accuracy and transparency in financial management and SIM as a solution to overcome the complexity of administrative and financial tasks for educational foundations.